2016
DOI: 10.1016/j.ijsu.2015.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Changes in surgical training opportunities in Britain and South Africa

Abstract: RSA has consistently offered more exposure to emergency, and especially trauma, surgery than the UK as well as more opportunity to act as primary operator. Re-introduction of "minor operations" lists for junior surgical trainees, acceptance of the importance for trainees to act as the primary operator, maintenance of the traditional "firm" structure and support for trainees who wish to spend a period of time abroad may help to improve clinical training and experience for UK surgical trainees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…14 A recent comparison of the surgical exposure of trainees in the United Kingdom (UK) and South Africa revealed that trainees in the UK experienced nearly double the amount of consultant supervision in theatre as those in SA. 15 The low level of supervision reported in this study may be due to the shortage of general surgical consultants in the public sector, and the pull of private practice for those working in both public and private sectors. Surgical training in South Africa remains Halsteadian in nature.…”
Section: Discussionmentioning
confidence: 69%
“…14 A recent comparison of the surgical exposure of trainees in the United Kingdom (UK) and South Africa revealed that trainees in the UK experienced nearly double the amount of consultant supervision in theatre as those in SA. 15 The low level of supervision reported in this study may be due to the shortage of general surgical consultants in the public sector, and the pull of private practice for those working in both public and private sectors. Surgical training in South Africa remains Halsteadian in nature.…”
Section: Discussionmentioning
confidence: 69%
“…This corresponds to an incidence of penetrating trauma of 16.4/ 100,000 and penetrating trauma related mortality of 0.6/100,000 per inhabitant [7]. Penetrating trauma accounts for only 5-10% of all trauma cases in Europe, compared with 40-50% in the United States of America (US) and South Africa [8][9][10]. The reality is that most European surgical programs are unable to provide trainees with sufficient exposure to penetrating and blast injuries.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of working time regulations over the past decade has been especially felt within surgery, resulting in a move away from the Halstedian model of training. [1,2] With less time available to train under the supervision of an expert in theatre, trainees now use more simulation-based medical education (SBME) alongside traditional methods, to develop surgical expertise. The use of SBME has advantages, particularly amongst trainee surgeons, who are able to develop basic skills with relative efficiency, and without compromising their own, or patient safety.…”
Section: Introductionmentioning
confidence: 99%